2021
DOI: 10.4049/immunohorizons.2100062
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Targeting the CD154 Cleavage Site Inhibits CD40-Dependent and -Independent Cleavage of CD154 from the Cell Surface

Abstract: In addition to the membrane-bound molecule, soluble CD154 (sCD154) is also detected at high levels in the medium of activated T cells and platelets and in the serum of patients suffering from different inflammatory diseases. This sCD154 is the result of cleavage of the full-length molecule between the glutamic acid residue at position 112 (E112) and methionine at position 113 (M113) and can be derived from the intracellular milieu and from cleavage of cell surface molecules. We have recently reported that subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Intracellular and membrane-bound CD154 (mCD154) molecules are prone to cleavage, releasing a soluble form involving residues 113-261, which is biologically active (trimeric) [ 20 ]. Studies by various groups, including ours, have demonstrated that soluble CD154 (sCD154) is released from activated platelets and T cells by proteolytic cleavage at its methionine residue at position 113 (M113), mediated by various members of the metalloproteinases family and initiated by the interaction of the ligand with CD40 in cleavage from T-cell surface ( Figure 1 ) and/or with αIIbβ3 in platelets cleavage [ 20 , 21 , 22 , 23 , 24 , 25 ]. Although the physiological role of sCD154 in vivo remains unclear, increased levels were reported in many inflammatory disorders [ 26 , 27 , 28 ].…”
Section: Cd154mentioning
confidence: 99%
“…Intracellular and membrane-bound CD154 (mCD154) molecules are prone to cleavage, releasing a soluble form involving residues 113-261, which is biologically active (trimeric) [ 20 ]. Studies by various groups, including ours, have demonstrated that soluble CD154 (sCD154) is released from activated platelets and T cells by proteolytic cleavage at its methionine residue at position 113 (M113), mediated by various members of the metalloproteinases family and initiated by the interaction of the ligand with CD40 in cleavage from T-cell surface ( Figure 1 ) and/or with αIIbβ3 in platelets cleavage [ 20 , 21 , 22 , 23 , 24 , 25 ]. Although the physiological role of sCD154 in vivo remains unclear, increased levels were reported in many inflammatory disorders [ 26 , 27 , 28 ].…”
Section: Cd154mentioning
confidence: 99%